STUDY ABOUT THE VARIABLES THAT TAKE PART IN THE PHYSICAL ABUSE OR CHILD NEGLIGENCE - Moreno Manso, Juan Manuel (Anales de Psicología / Annals of Psychology, 2002)
The scarcity of studies in the subject of physical abuse or negligence determines a really important ignorance of the child abuse typology, considered at the present time as that with the greatest incidence, either through national or international studies. Due to this fact, we try to give at biggest knowledge about a practice of children lacking of protection with such an unfavourable prognosis, through the analyses of nineteen social, relational and familiar individual variables.